Effect of pranayama and mindfulness meditation on emotional distress and fatigue in adult hematological cancer patients undergoing chemotherapy - Anjali Mangesh Joshi; Suchitra Ajay Mehta; Nishad Gajanan Dhakate; Ajay Omprakash Mehta (Wolters Kluwer Medknow Publications, 2023)
Introduction: Hematological cancer patients often experience anxiety, depression, and fatigue during chemotherapy. Addressing these issues can improve the quality of life and long-term well-being. This study evaluated the effects of pranayama and mindfulness meditation intervention on emotional distress and fatigue in hematological cancer patients undergoing chemotherapy. Materials and Methods: Adult hematological cancer patients undergoing chemotherapy (n = 27) were randomized into the intervention group (n = 12) or control group (n = 15). Baseline and post-6 weeks assessment was made using the Emotion Thermometer (ET) and Fatigue Assessment Scale (FAS). The intervention included daily practice of slow-paced pranayama and mindfulness meditation for 15 min each. Results: Statistical software SPSS v20.0 was used for data analysis. Within the intervention group, the pre-post comparisons indicated a statistically significant reduction in distress (p = 0.002), anxiety (p = 0.02), anger (p = 0.03), depression (p = 0.004), and need for help (p = 0.0005) scores of ET. Total fatigue (p = 0.002), physical fatigue (p = 0.002), and mental fatigue (p = 0.002) scores of FAS declined significantly within the intervention group. There was no statistically significant improvement for any parameter of ET or FAS within the control group. Between the groups, comparison showed a statistically significant reduction in distress (p = 0.004), anxiety (p = 0.02), anger (p = 0.03), need for help (p < 0.0005), total fatigue scores (p < 0.0001), physical fatigue (p < 0.0001), and mental fatigue (p < 0.0001) in the intervention group as compared to the control group. Conclusion: The results suggest the potential role of integrated pranayama and mindfulness meditation intervention in reducing emotional distress and fatigue in hematological cancer patients undergoing chemotherapy. Further validation with a larger sample size is required.